1988
DOI: 10.1161/01.str.19.9.1145
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane A2 in severe hypertension and stroke in stroke-prone spontaneously hypertensive rats.

Abstract: A 2 is a prostanoid having potent platelet aggregatory and vasoconstrictor properties. To determine a possible role for thromboxane A 2 in the development of severe hypertension and stroke, we chronically administered the selective thromboxane A 2 synthase inhibitor UK-38,485 (Dazmegrel) to stroke-prone spontaneously hypertensive rats (SHRSP). Serum thromboxane B 2 (the stable hydrolysis product of thromboxane A 2 ) generation was significantly greater in incubates of whole blood from SHRSP than in those from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…Histological examination revealed evidence of cerebrovascular lesions in all except one of the brains from control SHRSP. As previously observed, 21 these lesions included hematomas, hemorrhagic and anemic infarcts, edema and rarefaction of the cerebral cortex, and fibrinoid necrosis of vessels. There was no evidence of any of these lesions in the brains of enalapril-treated SHRSP.…”
Section: Analysessupporting
confidence: 78%
See 1 more Smart Citation
“…Histological examination revealed evidence of cerebrovascular lesions in all except one of the brains from control SHRSP. As previously observed, 21 these lesions included hematomas, hemorrhagic and anemic infarcts, edema and rarefaction of the cerebral cortex, and fibrinoid necrosis of vessels. There was no evidence of any of these lesions in the brains of enalapril-treated SHRSP.…”
Section: Analysessupporting
confidence: 78%
“…21 Despite lowering blood pressure by 15 to 29 mm Hg at 10 and 11 weeks of age during TXA 2 synthase inhibition, there was no effect on mortality; 70% of the animals with or without treatment died by 14 weeks of age. The ability of TXA 2 synthase inhibition to lower blood pressure without affecting mortality suggests that factors in addition to blood pressure may be important in causing stroke in these rats.…”
mentioning
confidence: 96%
“…ACE inhibition 15,21 and dietary potassium administration, 22 with no or only a small reduction in blood pressure, substantially prolonged survival in salt-loaded SHRSP. In contrast, a thromboxane A 2 synthase inhibitor, 23 hydralazine, and diuretics, 24 which all reduced blood pressure, did not prevent cerebral edema or significantly prolong survival.…”
Section: Early Therapymentioning
confidence: 90%
“…6). Although we previously found that chronic administration of the selective TSI UK-38,485 (dazmegrel) to saline-drinking SHRSP was associated with a slight reduction in systolic blood pressure, this also did not protect against stroke (63,64). Thus, agents that inhibit either the action or the formation of TxA 2 do not exhibit anti-stroke activity in these rats.…”
Section: Strokementioning
confidence: 93%